Analisis Perbandingan Kinerja Perusahaan Sebelum dan Sesudah Akuisisi : Studi pada Akuisisi PT Indofood CBP Sukses Makmur Tbk. Terhadap PT Arla Indofood Makmur Dairy Tbk. Periode 2016-2022 - Tara Audina; Eko Widodo; Aprilia Dian Evasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of variables, namely Current Ratio, Total Assets Turnover, Debt To Asset Ratio, Return On Assets, Sales Growth and Earning Per Shares on the company PT Indofood CBP Sukses Makmur Tbk before and after the Acquisition with PT Arla Indofood Makmur Dairy Tbk which has been listed on the Indonesia Stock Exchange in 2016-2022. The research location used in this study is PT, Indofood, Tbk. Where researchers will take data through financial reports on the Indonesia Stock Exchange. The analysis technique used is the Paired T-test. The results in this study indicate that the variables Current Ratio, Debt To Asset Ratio, Sales Growth and Earning Per Shares show significant differences between before and after the acquisition, while Total Assets Turnover, Return On Assets do not show significant differences between before and after the acquisition. With this research, it is hoped that the company can further improve various factors that do not have an effect in this study.